PENGUJIAN TEGANGAN TEMBUS MINYAK TRAFO DISTRIBUSI 20 kV DI PT. CHAROEN POKPHAND - Febrino Hotlinus Martua Siregar; Dwi Wahyu Sembiring; Beudwin Simbolon; Olnes Yosefa Hutajulu; Desman Jonto Sinaga (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The 20 kV distribution transformer is a critical component in maintaining the continuity of electrical supply in industrial operations, making routine evaluation of insulating oil quality essential to ensure system reliability. This study aims to analyze the dielectric condition of transformer oil by measuring its breakdown voltage and comparing the results with SPLN 49-1/1982 and IEC 56:1991 standards. Oil samples from three transformer units were tested using the Breakdown Voltage Test method with five repetitions to obtain representative average values. The results indicate that one transformer exhibited a breakdown voltage of 28.14 kV, which is below the minimum standard and signifies insulation degradation due to moisture and contamination. The other two transformers recorded values above 70 kV, indicating that their insulating oil remained in very good condition. These findings confirm that transformer physical conditions, moisture exposure, and maintenance practices significantly influence insulating oil performance. This study concludes that corrective actions such as leakage repair and oil purification are required to restore dielectric quality in the affected transformer unit.